Generalized Antiperiodic Boundary Value Problems for the Fractional Differential Equation with p-Laplacian Operator - Zhi-Wei Lv; Xu-Dong Zheng (Discrete Dynamics in Nature and Society)
We discuss the existence of solutions about generalized antiperiodic boundary value problems for the fractional differential equation with p-Laplacian operator , , , , , , where is the Caputo fractional derivative, , , , and , , , . Our results are based on fixed point theorem and contraction mapping principle. Furthermore, three examples are also given to illustrate the results.